P326 An exploratory analysis of the impact of COVID-19 on colonoscopy procedures and new biologic treatment initiation among patients with Inflammatory Bowel Disease in the United States. (27th May 2021) - Ungaro, R; Chou, B; Mo, J; Ursos, L; Twardowski, R; Candela, N; Colombel, J F
Abstract: Background: Patients with inflammatory bowel disease (IBD) require frequent colonoscopies to optimize disease management and treatment strategies. At the onset of the COVID-19 pandemic, many routine procedures were postponed to reduce the overall burden on healthcare systems. We characterized the impact of COVID-19 on IBD care by conducting an exploratory analysis of real-world US healthcare claims data to identify changes in treatment patterns and the number of colonoscopy procedures performed in patients with IBD during the first wave of the pandemic. Methods: De-identified, open-source health insurance claims data, from Jan 2019 to Oct 2020, were obtained from the Symphony Health Integrated Dataverse ® for US adults aged 18–80 years with IBD. Four outcome measures were used: number of colonoscopies performed; number of new biologic treatment initiations or treatment switches; number of new biologic treatment initiations or treatment switches in patients who had a colonoscopy within the previous 60 days; and rate of telehealth consultations per 1000 patients per month. Results: During Jan–Dec 2019 and Jan–Oct 2020, 1.54 million and 1.29 million patients with IBD, respectively, were included. The bimonthly number of colonoscopies remained stable throughout 2019, with a maximum change of +5.4% in Jul–Aug (N = 49947) vs Jan–Feb 2019 (N = 47399). Colonoscopy use decreased by 4.7% in Jan–Feb 2020 (N = 45167) vs the same period in 2019. In Mar–Apr 2020, colonoscopy numbers decreased by 55.3% (N = 20191) vs Jan–Feb 2020 (Figure 1a ); a reduction of 59.4% vs Mar–Apr 2019 (N = 49780). In May–Jun 2020 (−23.8%) and Jul–Aug 2020 (+2.0%) the difference vs Jan–Feb 2020 gradually decreased (Figure 1a ). Bimonthly numbers of new treatment initiations or treatment switches in 2019 varied by up to 6.9% vs Jan–Feb 2019. In May–Jun 2020, numbers of new treatment initiations or treatment switches decreased by 17.0% (N = 10072) vs Jan–Feb 2020 (N = 12133) (Figure 1b ); a decrease of 19.3% vs May–Jun 2019 (N = 12488). The number of new treatment initiations or treatment switches in patients who had a colonoscopy within the previous 60 days decreased by 42.5% (N = 892) in Mar–Apr 2020 vs Jan–Feb 2020 (N = 1551) (Figure 1c ); a decrease of 44.2% vs Mar–Apr 2019 (N = 1599). Telehealth utilization increased in March 2020 and remained higher than in 2019 up to October 2020 (Figure 2 ). Conclusion: Reduction in colonoscopies and subsequent initiation/switching of treatments during the COVID-19 pandemic first wave suggests lost opportunities for therapy optimization that may have an impact on longer-term patient outcomes. Increased utilization of telehealth services may have helped address gaps in routine clinical care.